Greed and Grievance in Civil War - Collier, Paul (World Bank, Washington, DC, 2014)
The authors compare two contrasting motivations for rebellion: greed and grievance. Most rebellions are ostensibly in pursuit of a cause, supported by a narrative of grievance. But since grievance assuagement through rebellion is a public good that a government will not supply, economists predict such rebellions would be rare. Empirically, many rebellions appear to be linked to the capture of resources (such as diamonds in Angola, and Sierra Leone, drugs in Colombia, and timber in Cambodia). The authors set up a simple rational choice model of greed-rebellion, and contrasts its predictions with those of a simple grievance model. Some countries return to conflict repeatedly. Are they conflict-prone, or is there a feedback effect whereby conflict generates grievance, which in turn generates further conflict? The authors show why such a feedback effect might be present in both greed-motivated and grievance rebellions. The authors' results contrast with conventional beliefs, about the causes of conflict. A stylized version of conventional beliefs would be that grievance begets conflict, which begets grievance, which begets further conflict. With such a model, the only point at which to intervene is to reduce the level of objective grievance. The authors' model suggests that what actually happens is that opportunities for predation (controlling primary commodity exports) cause conflict, and the grievances this generates induce diasporas to finance further conflict. The point of policy intervention here is to reduce the absolute, and relative attraction of primary commodity predation, and to reduce the ability of diasporas to fund rebel movements.